Agriculture in the Uruguay Round : an assessment. - RAYNER, A.J. (1993)
Explains the factors which have made agriculture such an important issue. Points out the fragility of the Washington accord (US-EC), and emphasises the importance of a settlement in securing real liberalisation in a sheltered sector and in constraining future changes in domestic farm programmes.